19 - STUDY OF EXERCISE CAPACITY, THE TEST DISTANCE TRAVELED IN SIX MINUTES (DP6MIN) IN PATIENTS WITH LEPROSY (Fiep Bulletin - online, 2011)
Introduction: Leprosy is an infectious disease transmitted from person to person through contact among susceptible to infectious patients. It commits the peripheral nerves leading to disability and impairment to the individual, and generates motor abnormalities such as atrophy, paralysis and joint locks. The test of distance walked in six minutes (DP6min) evaluates the functional exercise at submaximal and was therefore chosen to evaluate the exercise capacity of patients in this study. Objective: To evaluate the exercise capacity of patients suffering from leprosy, the test of distance walked in six minutes (DP6min) in the physiotherapy clinic at State University of West of Paraná - UNIOESTE. Methods: The DP6min was applied in 9 subjects above 18 years of age diagnosed with leprosy, and 3 females, mean age of 52.78 ± 10 years. Results: The average distance traveled by patients was 516.6 ± 28 during the course of DP6min. Conclusion: Despite the deformities and physical disabilities of patients with sequel of leprosy, the ability to exercise the same is similar to the ability of healthy individuals.
Keywords: Leprosy; exercise capacity; disability